2017
DOI: 10.1097/qad.0000000000001417
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of life with immediate versus deferred initiation of antiretroviral therapy in early asymptomatic HIV infection

Abstract: Objective To determine if immediate compared to deferred initiation of antiretroviral therapy (ART) in healthy persons living with HIV (PLWH) had a more favorable impact on health-related quality of life (QOL), or self-assessed physical, mental and overall health status. Design QOL was measured in START (Strategic Timing of Antiretroviral Therapy), which randomized healthy ART naive PLWH with >500 CD4+ cells/μl from 35 countries to immediate versus deferred ART. Methods At baseline, months 4 and 12, then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 24 publications
2
58
2
2
Order By: Relevance
“…Clinical and implementation research continue to provide important insights into the effectiveness of treating all persons living with HIV. Data from the START trial have found that immediate ART led to improved quality of life [15], and the programmatic benefits of early and rapid ART initiation in terms of reducing pre-ART loss-to-care can be substantial [13, 16,17]. Notwithstanding these benefits, there are important programmatic challenges to achieving the full benefits of Treat All.…”
mentioning
confidence: 99%
“…Clinical and implementation research continue to provide important insights into the effectiveness of treating all persons living with HIV. Data from the START trial have found that immediate ART led to improved quality of life [15], and the programmatic benefits of early and rapid ART initiation in terms of reducing pre-ART loss-to-care can be substantial [13, 16,17]. Notwithstanding these benefits, there are important programmatic challenges to achieving the full benefits of Treat All.…”
mentioning
confidence: 99%
“…Among 305,443 PLHIV included in the analysis, 118,580 (38.8%) had a CD4+ ≥200 cells/mm 3 at ART initiation (median of 285 cells/mm 3 , interquartile range: 237 to 349 cells/mm 3 ) and the remaining 186,863 (61.2%) PLHIV had low CD4+ (<200 cells/mm 3 At 12 months after ART initiation, 21.3% (95% CI 21.1 to 21.6) of PLHIV with CD4+ ≥200 cells/mm 3 had been LTF or had died compared to 21.8% (95% CI 21.6 to 22.1) among those with CD4+ 100 to 199 cells/mm 3 , 27.3% (95% CI 26.9 to 27.7) among those with CD4+ 50 to 99 cells/mm 3 and 33.6% (95% CI 33.2 to 34.0) among those with CD4+ <50 cells/mm 3 ( Table 2). In multivariable models, compared to PLHIV with CD4+ ≥200 cells/mm 3 , those with CD4+ 100 to 199 cells/mm 3 had 9% increased risk of attrition (adjusted hazard ratio (AHR) 1.09, 95% CI 1.07 to 1.11), those with CD4+ 50 to 99 cells/mm 3 had 29% increased risk of attrition (AHR 1.29, 95% CI 1.27 to 1.32) and PLHIV with CD4+ <50 cells/mm 3 had 56% increased risk (AHR 1.56, 95% CI 1.53 to 1.58) ( Figure 1a, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…АРВТ позитивно отражается на качестве жизни, что, в свою очередь, может улучшать психическое состояние, особенно при раннем начале АРВТ [13]. Если человек жалуется на тревогу или депрессию, ему следует обратиться к психиатру или психотерапевту.…”
Section: депрессия или тревожные состоянияunclassified